The Challenges of Greenpeace Indonesia's Supports on One Map Policy Indonesia - Nurhidayah, Gita (Journal of International Relations on Energy Affairs, 2022)
As a branch of international non-governmental organization (NGO), Greenpeace Indonesia has been supporting the policy of One Map Policy (OMP) Indonesia since 2017. This policy is essential to manage the forestry and land in Indonesia as deforestation is rising. Despite comprehensive support to OMP, Greenpeace Indonesia did not successfully push the Indonesian government to take severe attempts for the OMP legalization. This paper examines the challenges that Greenpeace Indonesia faces in this support. We elaborate on this problem by explaining it through the theory of International NGO Challenges in policy engagement. This theoretical framework is usually used to describe any possible opportunities and challenges for non-state actors to influence government policies. Our research is based on the literature review with the qualitative method. We argue that Greenpeace Indonesia has several challenges that hinder its support of OMP Legalization. Those are both internal coordination and external condition, especially regarding the advocacy system in Indonesia.